Relationships between salivary testosterone and cortisol concentrations and training performance in Olympic weightlifters - Crewther, B. T.; Cook, C. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: This study examined the relationships between salivary testosterone (Sal-T) and cortisol (Sal-C) concentrations and training performance in Olympic weightlifters. METHODS: Four male and four female Olympic weightlifters each provided saliva samples before and after four workouts during a four-week training period. Training involved the same three exercises; snatch, clean and jerk, and front squat with the one repetition maximum (1RM) calculated for each exercise during each workout. RESULTS: Significant (P < 0.05-0.01) training improvements in 1RM performance (4.0-5.2%) were noted during the snatch and clean and jerk exercises, along with the Olympic total lift. For male participants only, the pre-workout concentrations of Sal T were significantly (P < 0.05-0.01) correlated with the snatch (r = 0.70) and clean and jerk 1RM (r = 0.62), and the Olympic total lift (r = 0.66). CONCLUSION: A short period of training improved the 1RM performance of Olympic weightlifters in two exercises (snatch and clean and jerk) and the Olympic total. For male participants, their Sal-T concentrations before each workout was also related to 1RM performance during these exercises, thereby highlighting one possible short-term causative mechanism. Limitations of this study include the short duration of hormonal monitoring, the limited number of workouts assessed and the small number of participants recruited. Also, correlations between the outcome variables still only reflect casual associations.